ISUASPHAERA ISUA (PFLUG) REVISITED - Appel P.W.U.; Moorbath S.; Myers J.S. (My University, 2003)
Spherical objects, identified as microfossils and named Isuasphaera isua (Pflug), were reported in 1978 from a chert in the 3.7-3.8Ga Isua Greenstone Belt (IGB). Soon afterwards the biological nature of these objects was questioned on a number of grounds by several authors.Following renewed, recent claims for biogenicity, the locality has been revisited and the host-rock (metamorphosed chert) to the putative microfossils re-examined. Extreme stretching deformation of the metachert cannot possibly have preserved syn-depositional spherical objects. We conclude that the objects (whether biological or not) are entirely post-tectonic and probably result from pre-Quaternary weathering.
Keywords: MICROFOSSILS; ISUASPHAERA ISUA; ISUA GREENSTONE BELT; Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная